FAUST VI. VLA1623−2417 B: a new laboratory for astrochemistry around protostars on 50 au scale. Issue 1 (30th June 2022) - Codella, C; López-Sepulcre, A; Ohashi, S; Chandler, C J; De Simone, M; Podio, L; Ceccarelli, C; Sakai, N; Alves, F; Durán, A; Fedele, D; Loinard, L; et al.
ABSTRACT: The ALMA (Atacama Large Millimeter Array) interferometer, with its unprecedented combination of high sensitivity and high angular resolution, allows for (sub-)mm wavelength mapping of protostellar systems at Solar system scales. Astrochemistry has benefitted from imaging interstellar complex organic molecules in these jet–disc systems. Here, we report the first detection of methanol (CH3 OH) and methyl formate (HCOOCH3 ) emission towards the triple protostellar system VLA1623−2417 A1+A2+B, obtained in the context of the ALMA Large Programme FAUST (Fifty AU STudy of the chemistry in the disc/envelope system of solar-like protostars). Compact methanol emission is detected in lines from E u = 45 K up to 61 K and 537 K towards components A1 and B, respectively. Large velocity gradient analysis of the CH3 OH lines towards VLA1623−2417 B indicates a size of 0.11–0.34 arcsec (14–45 au), a column density $N_{\rm CH_3OH}$ = 10 16 –10 17 cm −2, kinetic temperature ≥ 170 K, and volume density ≥ 10 8 cm −3 . A local thermodynamic equilibrium approach is used for VLA1623−2417 A1, given the limited E u range, and yields T rot ≤ 135 K. The methanol emission around both VLA1623−2417 A1 and B shows velocity gradients along the main axis of each disc. Although the axial geometry of the two discs is similar, the observed velocity gradients are reversed. The CH3 OH spectra from B show two broad (4–5 km s −1 ) peaks, which are red- and blueshifted by ∼ 6–7 km s −1 from the systemic velocity. Assuming a chemically enriched ring within the accretion disc, close to the centrifugal barrier, its radius is calculated to be 33 au. The methanol spectra towards A1 are somewhat narrower (∼ 4 km s −1 ), implying a radius of 12–24 au.